2020
DOI: 10.3390/biom10121607
|View full text |Cite
|
Sign up to set email alerts
|

The Human Epidermal Basement Membrane: A Shaped and Cell Instructive Platform That Aging Slowly Alters

Abstract: One of the most important functions of skin is to act as a protective barrier. To fulfill this role, the structural integrity of the skin depends on the dermal-epidermal junction—a complex network of extracellular matrix macromolecules that connect the outer epidermal layer to the underlying dermis. This junction provides both a structural support to keratinocytes and a specific niche that mediates signals influencing their behavior. It displays a distinctive microarchitecture characterized by an undulating pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 303 publications
1
57
0
1
Order By: Relevance
“…In the current study, there was an increase in basement membrane thickness in all examined cases. This was in agreement with an ultrastructural study by Roig-Rosello and Rousselle (20) as normal dermal nerves are performed. Also, Stylianos et al (21) reported that, in vitiligo it is well-documented that epidermis is thicker than in normally pigmented skin in frozen sections and that inflammatory changes are more frequent and intense in the epidermis and dermis of perilesional skin.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, there was an increase in basement membrane thickness in all examined cases. This was in agreement with an ultrastructural study by Roig-Rosello and Rousselle (20) as normal dermal nerves are performed. Also, Stylianos et al (21) reported that, in vitiligo it is well-documented that epidermis is thicker than in normally pigmented skin in frozen sections and that inflammatory changes are more frequent and intense in the epidermis and dermis of perilesional skin.…”
Section: Discussionsupporting
confidence: 91%
“…Between the epidermis and dermis, there is a cutaneous basement membrane zone, which connects basal keratinocytes with collagen fibers located on the surface of the dermis [ 36 ]. The main function of this structure is to provide adhesion between both layers, Since the epidermis is avascular, the basement membrane zone allows oxygen and nutrient exchange from the vascular dermis to the epidermis [ 37 ].…”
Section: Skin Structurementioning
confidence: 99%
“…The collagen IV protein represents 50% of all basement membrane [63] and provides structural stability to the basement membrane [59]. However, aging significantly reduces collagen IV expression in the dermal-epidermal junction [58,64] and the lack of collagen IV can promote scar pathogenesis [65]. Thus, our results suggest that the increased basement membrane regenerative potency of the ADSCsladen gene-activated scaffold can significantly aid in enhanced healing in aged patients.…”
Section: Discussionmentioning
confidence: 75%